Peningkatan Kompetensi Guru SLB Negeri Bugih Pamekasan Melalui Pemanfaatan Media Pembelajaran dan Aplikasi Belajar Online - Shefa Dwijayanti Ramadani; Agus Budiyono; Masdukil Makruf (Jurnal Pemberdayaan Masyarakat, 2021)
The conditions of the Covid-19 pandemic caused extraordinary changes in various sectors of life, including in the education sector. The closure of all school institutions "forced" the teachers transform their learning into online learning to reduce the potential spread of the Corona Virus in one school environment. Unfortunately, it had been a year after the implementation of learning from home began; the challenges and obstacles in implementing online learning were still felt at SLB Negeri Bugih Pamekasan. This community service aims to improve the ability of teachers to create and use learning media, as well as using online learning applications to support the learning process during pandemic situation. The method used was training which was packaged in a Focus Group Discussion (FGD) format. The results of the activity showed that: (1) 100% of teachers were able to use information and communication technology, especially the internet to find digital learning media that suits student needs, (2) 80% of teachers were able to make simple learning videos, and (3) 100% of teachers were able to use online learning applications to support the learning process.